Upgrading model for the Volleyball teachers - Tania Rosa García Hernández; Ídolo Gilberto Herrera Delgado; Modesta Moreno Iglesias; Luis Alberto Cuesta Martínez; Luis Manuel Barrera Pardo (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2017)
The nowadays society in this XXI century influenced by the progressive development of technologies of information and communication and the knowledge management demands a creative man, transformer of the context in which he takes place, an individual who accepts the challenges of the modern society and that at the same time takes the best of this development. Meeting this goal, the higher education holds the mission of preparing in a continuous and permanent way to the professionals according to the activity they carry out, updating the knowledge in the science they work on. The sport professionals are not the exception in this endeavor due to the formative role they play in the society, it is also caused by the dynamics and the current competitions, the steady changes of the sport rules and the gradual improvement of the athlete's performance, the venues equipment and the competition itself worldwide. This work is aimed at proposing an upgrading course for the Volleyball professionals in the sport formation school (EIDE) Ormani Arenado Llonchimplemented through a strategy based on the difficulties taken from the application of the scientific methods which facilitate a viable, flexible and feasible outcome and with a high social meaning, as it contributes to rise the professional profile of the individuals involved in the study.